(untitled) (Economic and Political Thought, 2012)
The subject matter of the article is the analysis of the course of diplomatic struggle for the institutional shape and character of the process of uniting Western European countries in the years 1955–1960. It was a special period in the history of the European integration. That was when the countries of Western Europe formally split into two groups having two different ideas of how to unite Europe. Creating the EEC and the EFTA was an institutional manifestation of that division. The former had some incorporated mechanisms of supranational integration requiring a cession of sovereignty. The latter was heading for gradual abolition of trade restrictions and coordination of sovereign countries’ economic policy. The differences in the interests and stands of particular states that appeared then have not lost their importance until now. The article presents an analysis and interpretation of the European integration that differs strongly from the type dominating in science. It is not aimed at characterizing the content and shape of the ready-made product of the integration idea like the EEC and the EFTA. It shows the other side of the picture, i.e. the course of long-lasting and very strong British diplomatic struggle for halting the pace and range of supranational integration of Western Europe and explains the reasons of British failures in the field. It turns out that, in the British policy regarding the European integration, the factor of continuity prevails over the factor of changes.